MORFOLOGI ARSITEKTUR MASJID DI DENPASAR BALI - Ardiansyah, Ardiansyah (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 2 No 2 (2015): Oktober 2015, 2015)
Abstract The mosque is the sacred building of Moslems and its architectural design is influenced by its environment. As a result, mosques in every area have a unique morphology. In South-East Asia roofs tend to be layered as in Indonesia. As such, many debates occur as to its origins. Three basic theories exist. Firstly, the design may be affected by peripheral elements, such as Malabar. Secondly, Javanese mosques have affected Indonesian style, even in Asia. Thirdly, local wisdom is an essential element in Mosque design. The study reveals local cultures have affected the morphology of the mosque in Denpasar. For instance, it can be identified through the concept of open space; the use of wantilan and bale ; colours of building performance, ornaments, and interior decorations. Qualitative methodology is used in data analysis. Furthermore, the study discoveres that an understanding of the hadist plays an important role in th ecreation of mosque morphology in Denpasar. Keywords: mosque, morphology, culture, environment, hadist Abstrak Masjid merupakan bangunan suci umat Islam yang tampilan arsitekturalnya dipengaruhi oleh lingkungan, sehingga tiap daerah memiliki morfologi masjid yang berbeda-beda. Salah satu morfologi masjid yang mewakili Asia Tenggara adalah masjid beratap tumpang yang banyak ditemukan di Indonesia. Namun demikian, terdapat banyak perdebatan mengenai asal-usul tipologi masjid tersebut. Beberapa penelitian morfologi masjid di Indonesia menunjukkan tiga teori dasar mengenai asal-usul bentuk masjid di Indonesia. Pertama, masjid di Indonesia dipengaruhi oleh arsitektur dari luar, seperti Malabar. Kedua, arsitektur masjid di Indonesia, bahkan di  Asia, dipengaruhi oleh arsitektur masjid Jawa; sedangkan ketiga, arsitektur masjid lahir dari kearifan lokal setempat. Studi ini mengungkapkan bahwa budaya lokal Kota Denpasar mempengaruhi morfologi masjid, seperti konsep ruang terbuka, penggunaan bentuk bale dan wantilan , warna, dan ragam hias. Metode kualitatif deskriptif digunakan untuk mengeksplorasi data dan menganalisisnya. Studi ini juga mengungkapkan bahwa pemahaman terhadap hadist berperan penting dalam menciptakan morfologi masjid di Denpasar. Kata kunci: m asjid, m orfologi, b udaya, l ingkungan, h adist
Keywords: masjid; morfologi; budaya; lingkungan; hadist